1998
DOI: 10.1007/s004380050777
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin genes of Methanococcus vannielii : amplification by the Polymerase Chain Reaction, demonstration of signal peptides and identification of major components of the flagellar filament

Abstract: The highly conserved nature of the 5'-termini of all archaeal flagellin genes was exploited by polymerase chain reaction (PCR) techniques to amplify the sequence of a portion of a flagellin gene family from the archaeon Methanococcus vannielii. Subsequent inverse PCR experiments generated fragments that permitted the sequencing of a total of three flagellin genes, which, by comparison with flagellin genes that have been sequenced, from other archaea appear to be equivalent to flaB1, flaB2, and flaB3 of M. volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Comparison of the N-terminal sequence of one purified flagellin with the amino acid sequence predicted from the gene sequence (13) confirmed the presence of a 12-amino-acid leader peptide. Similarly, in the related methanogen Methanococcus vannielii, comparison of the N-terminal sequences obtained from the two major flagellins of purified flagellar filaments with the deduced amino acid sequence of the cloned genes indicated the presence of 12-amino-acid leader peptides on the FlaB1 and FlaB2 flagellins (2). The presence of leader peptides on archaeal flagellins indicated that enzymatic activity must be present in archaeal cells to process the preflagellins.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Comparison of the N-terminal sequence of one purified flagellin with the amino acid sequence predicted from the gene sequence (13) confirmed the presence of a 12-amino-acid leader peptide. Similarly, in the related methanogen Methanococcus vannielii, comparison of the N-terminal sequences obtained from the two major flagellins of purified flagellar filaments with the deduced amino acid sequence of the cloned genes indicated the presence of 12-amino-acid leader peptides on the FlaB1 and FlaB2 flagellins (2). The presence of leader peptides on archaeal flagellins indicated that enzymatic activity must be present in archaeal cells to process the preflagellins.…”
mentioning
confidence: 97%
“…However, recent evidence has indicated that the archaeal flagellum is a unique motility structure, distinct from that of bacteria in composition and likely assembly (4,10). One major distinction is that the assembly of archaeal flagella requires the posttranslational cleavage of a short (11-or 12-amino-acid) leader peptide (2,13) from the precursor form of the flagellin monomer (preflagellin) before its incorporation into the growing filament. Bacterial flagellins are not made with leader peptides (12).…”
mentioning
confidence: 99%
“…It has been demonstrated for some methanogens that leader peptides are cleaved from preflagellins upon export (2,14,24). This is likely true of all archaeal flagellins, based on sequence alignments (45).…”
mentioning
confidence: 98%
“…Although the multiple flagellin genes within a particular family share considerable sequence similarity, mutant studies with Methanococcus voltae and H. salinarum suggest that the proteins encoded by the multiple flagellin genes are not simply interchangeable and likely have specific roles within the filament (23,44). This is supported by the fact that archaeal flagellar filaments tend to be composed of a mixture of different flagellins, present in varying amounts (2,16).…”
mentioning
confidence: 99%
“…Archaeal flagellins are synthesized with a leader peptide (3,18), which is cleaved prior to the incorporation of the flagellin into the filament, similar to the processing of type IV pilins before incorporation into the pilus (34). A Methanococcus maripaludis protein (FlaK) possessing preflagellin peptidase activity has recently been reported (2).…”
mentioning
confidence: 99%